IN VIVO ANTI OXIDATIVE EFFECT OF POLYHERBAL FORMULATION OF FLAX SEED, FENUGREEK AND JAMUN SEED ON STREPTOZOTOCINNICOTINAMIDE INDUCED DIABETIC RATS - S.LATHA,; R.VIJAYAKUMAR,; B.R.SENTHIL KUMAR,; R.SRIKUMAR, (International Journal of Pharma and Bio Sciences, 2016)
Oxidative stress is the main cause of the secondary complications in diabetes mellitus (DM). The aim of this study is to evaluate the antioxidative effect of polyherbal formulation (PHF) of hydroalcoholic extracts of flaxseed, fenugreek, jamun seed (1:1:1) and their individual drugs in Streptozotocin-Nicotinamide induced DM in wistar rats. The drugs were given orally at dose of 200mg/kg body weight (bw )for 30 days .On 31st day liver were isolated and homoginized in Tris-HCl buffer for measurement of antioxidants. The result shown that significant (p<0.05) increase in lipid peroxidation and decrease in suproxide dismutase, catalase, glutathione peroxidase, glutathione s transferase, glutathione reductase, vitamin C, vitamin E level in diabetic animals. The treatment with PHF and their individual drugs significantly reversed these changes. The PHF treated group shown greater percentage changes than their individual drugs treated groups. This concludes PHF has greater antioxidative effect and the synergism exist between their individual drugs.